2019
DOI: 10.1111/cp.12170
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐session cognitive behaviour therapy for eating disorders: Outcomes from a pragmatic pilot study of Australian non‐underweight clients

Abstract: Background: Ten-session cognitive-behavioural therapy (CBT-T) for eating disorders is designed to reduce barriers to treatment, including cost, therapist expertise, and lengthy wait lists. The current study aimed to replicate the first case series, evaluating the effectiveness of CBT-T in a sample of non-underweight clients, delivered by trainee psychologists under expert supervision.Methods: CBT-T was delivered to 26 clients in an outpatient setting. Outcomes included eating disorder cognitions and behaviours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 37 publications
7
21
0
Order By: Relevance
“…The reduction in the client's global EDE-Q score (2.5) was comparable to the improvements observed within CBT-T treatment studies (2.6, Pellizzer, Waller, & Wade, 2018;1.97, Waller et al, 2018). The client's EDE-Q subscale scores reduced to below the clinical cut-off at follow-up.…”
Section: Discussionsupporting
confidence: 65%
“…The reduction in the client's global EDE-Q score (2.5) was comparable to the improvements observed within CBT-T treatment studies (2.6, Pellizzer, Waller, & Wade, 2018;1.97, Waller et al, 2018). The client's EDE-Q subscale scores reduced to below the clinical cut-off at follow-up.…”
Section: Discussionsupporting
confidence: 65%
“…There were also improvements in secondary outcomes, such as depression and anxiety symptoms. A subsequent small case series design replicated these findings (Pellizzer, Waller, & Wade, ).…”
Section: Introductionmentioning
confidence: 61%
“…The overall aim of the current study is to explore the effectiveness of outpatient CBT‐T delivered by trainee psychologists in an Australian sample of transdiagnostic patients with eating disorders. A key step in developing new therapies is establishing replicability (Open Science Collaboration, ), and therefore, replicating the Waller et al () and Pellizzer et al () findings is an important first aim. This is especially important as the majority of prior effectiveness studies of CBT have predominantly used experienced therapists (Byrne et al, ; Knott et al, ; Signorini, Sheffield, Rhodes, Fleming, & Ward, ; Waller et al, ) with few using clinical assistants and inexperienced therapists from varying fields (Rose & Waller, ; Turner et al, ; Waller et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…CBT‐T has strong clinical outcomes, comparable to those from other forms of CBT‐ED (Pellizzer et al, in press; Waller et al, ). This study has shown that patients also experience the therapy positively in terms of outcome and alliance.…”
Section: Discussionmentioning
confidence: 88%
“…Such a brief therapy has recently been developed in the field of eating disorders, in the form of a 10‐session CBT‐T for non‐underweight patients with eating disorders (Waller et al, ). At half the length of existing recommended versions of CBT for eating disorders (e.g., Fairburn, ; Waller et al, ) and achieving comparable results (Pellizzer, Waller, & Wade, in press; Waller et al, ), CBT‐T has the potential to achieve those improvements in cost and access. However, although CBT‐T results in positive therapeutic alliance scores (Waller et al, ), it remains to be seen how patients experience this new, brief therapy.…”
Section: Introductionmentioning
confidence: 99%